Neuropsychiatric Symptoms in Pediatric Chronic Pain and Outcome of Acceptance and Commitment Therapy - Balter, Leonie J. T.; Wiwe Lipsker, Camilla; Wicksell, Rikard K.; Lekander, Mats (Frontiers in Psychology, 2021)
Considerable heterogeneity among pediatric chronic pain patients may at least partially explain the variability seen in the response to behavioral therapies. The current study tested whether autistic traits and ADHD symptoms in a clinical sample of children and adolescents with chronic pain are associated with socioemotional and functional impairments and response to Acceptance and Commitment Therapy (ACT) treatment, which has improving psychological inflexibility as its core target. Children and adolescents aged 8-18 (N = 47) were recruited. Patients and their parents completed questionnaires pre- and post-ACT of 17 sessions. Mixed effects models and correlational analyses were used to assess the role of autistic traits and ADHD symptoms in pre-treatment functioning and ACT-treatment response. Outcome variables were degree to which pain interfered with daily activities (i.e., pain interference, sleep, and physical and school functioning), socioemotional functioning (i.e., depressive symptoms, emotional and social functioning), psychological inflexibility, and pain intensity. Autistic traits and ADHD symptoms, pain frequency, and pain duration were measured at pre-treatment only. All outcome variables, except for sleep disturbances and school functioning, significantly improved from pre- to post-ACT. Higher autistic traits were associated with greater pain interference, higher depression, and greater psychological inflexibility. Higher autistic traits were associated with greater improvements in emotional functioning and sleep disturbance, and non-significant improvements in pain interference, after treatment. Higher ADHD symptomatology was associated with greater pre-treatment pain interference, lower emotional functioning, greater depression, and longer duration of pain. ADHD symptomatology was not associated with treatment outcome. The current results showed that neuropsychiatric symptoms in pediatric chronic pain patients are linked to lower functioning, particularly pain interfering with daily life and lower socioemotional functioning. The results suggest that not only pediatric chronic pain patients low in neuropsychiatric symptoms benefit from ACT but also those high in autism traits and ADHD symptoms. Patients higher in autistic traits may even extra benefit from ACT. Future research may assess whether improvements in psychological inflexibility, the core focus of ACT, enabled those higher in autism traits to gain more from the treatment.